The Influence of Service Quality on Repurchase Intention with Customer Satisfaction as a Mediating Variable. Study on Traveloka - Munawwarah, Lulu Al; Permadi, Lalu Adi (Raudhah Publisher, 2025)
This study aims to examine the effect of service quality on repurchase intention with customer satisfaction as a mediating variable in the study on Traveloka. The criteria for being used as a sample in this study are people domiciled in NTB who have made online purchases on Traveloka with at least one transaction. Through a quantitative approach, this study will collect data using an online questionnaire to 100 respondents with a sample collection technique in the form of simple random sampling. This study uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) data analysis method with the help of Smart-PLS software version 4.0. The results of the study indicate that Service Quality does not have a significant effect on Repurchase Intention, but on Consumer Satisfaction it has a significant effect. Customer Satisfaction has a significant effect on Repurchase Intention, and Customer Satisfaction can mediate Service Quality on Repurchase Intention.